Examining the paradoxical effects of kratom: a narrative inquiry - Smith, Kirsten E.; Feldman, Jeffrey D.; Dunn, Kelly E.; McCurdy, Christopher R.; Weiss, Stephanie T.; Grundmann, Oliver; Garcia-Romeu, Albert; Nichels, Janeen; Epstein, David H. (Frontiers in Pharmacology, 2023)
Introduction: Surveys and case reports have documented kratom use in the United States (US) for over a decade. However, those reports have generally not examined in depth the role kratom plays in the lives of those who use it regularly for sustained periods. Until there are controlled studies of the pharmacology and subjective effects of kratom alkaloids in humans, one of the best sources of insight on kratom-product use remains qualitative data with nuanced descriptions of kratom effects from those who use it regularly. Method: We conducted semistructured qualitative interviews with adults who regularly use kratom products, as part of a laboratory study of kratom-product self-administration. This qualitative component of the study was conducted as a narrative case-report series (n = 10). Results: Despite some differences among participants, all experienced acute combination effects that were largely, even simultaneously, analgesic and stimulatory. Most participants had decreased their dosages over time, and one planned to quit. Five of the 10 participants met DSM-5-based criteria for kratom-use disorder (3 mild, 1 moderate, 1 severe, by symptoms counts). When kratom was inadvertently taken in larger than intended doses, participants described a constellation of symptoms that they called “the wobbles” (a jittery feeling accompanied by what seemed to be nystagmus); this was rare, but could be of scientific and clinical interest as a possible manifestation of serotonin syndrome. Most participants described tolerance but considered kratom generally safe at low-moderate doses, providing perceived benefits with less potential risk for adverse effects compared to pharmaceuticals or illicit drugs. Discussion: In-depth interview data like these help confirm and clarify findings from larger survey studies and clinician-driven case reports. They are needed to inform the policy practice regarding kratom and may also help inform future experimental designs.